Application of IoT for The Learning Process in All Private Universities - Rumba, Maria Florentina; Dasilva, Gregoriany C. K. Dessy (Universitas Negeri Semarang, 2022)
Currently Indonesia is in the industrial era 4.0 which allows all non-computer objects to be connected to the internet. The development of industry 4.0 has penetrated the world of education. IoTs that support the learning process in class include smart presents, room temperature settings, automatic light settings, interactive whiteboards, study desks and IoT chairs. East Nusa Tenggara is one of the provinces in Indonesia which has several private universities, of course it is necessary to know the extent of the application of IoT’s which supports the learning process in the classroom. This type of research is quantitative descriptive using statistical descriptive analysis methods to determine the application of IoT in the process of learning activities in the classroom. The population in this study were all private universities scattered throughout the East Nusa Tenggara region. The criteria for the sample were private universities that were accredited B which were scattered in the East Nusa Tenggara region, as well as the office holders. The results of the study show that there are 3 categories of using IoT applications on private campuses in East Nusa Tenggara, namely high, medium and low categories. The results of this study will be a benchmark for the Ministry of Education to assess the most popular and frequently used IoT applications by users in all private campuses in East Nusa Tenggara and become a form of special attention to increase skills and awareness in the use of IoT applications as an awareness of change. 4.0 in education.